The gilded cage : technology, development, and state capitalism in China - Lei, Ya-Wen (Princeton, New Jersey : Princeton University Press, 2023)
"How China's economic development combines a veneer of unprecedented progress with the increasingly despotic rule of surveillance over all aspects of life. Since the mid-2000s, the Chinese state has increasingly shifted away from labor-intensive, export-oriented manufacturing to a process of socioeconomic development centered on science and technology. Ya-Wen Lei traces the contours of this techno-developmental regime and its resulting form of techno-state capitalism, telling the stories of those whose lives have been transformed-for better and worse-by China's rapid rise to economic and technological dominance. Drawing on groundbreaking fieldwork and a wealth of in-depth interviews with managers, business owners, workers, software engineers, and local government officials, Lei describes the vastly unequal values assigned to economic sectors deemed "high-end" versus "low-end," and the massive expansion of technical and legal instruments used to measure and control workers and capital within them. She shows how China's rise has been uniquely shaped by its time-compressed development, the complex relationship between the nation's authoritarian state and its increasingly powerful but unruly tech companies, and an ideology that fuses nationalism with high modernism, technological fetishism, and meritocracy. Some have compared China's extraordinary transformation to America's Gilded Age. This provocative book reveals how it is more like a gilded cage, one in which the Chinese state and tech capital are producing rising inequality and new forms of social exclusion"--
Introduction -- From labor to land and technology -- The turn to techno-development -- Obsolete capital and labor -- Robotization -- The rise of big tech -- From factories to platforms -- Coding elites -- Rewiring techno-state capitalism -- Conclusion
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 29, 2023).
JSTOR
Keywords: Economic development -- China; Technological innovations -- China; Capitalism -- China; Développement économique -- Chine; Innovations -- Chine; business (commercial function); economics; labor; social classes; social sciences; e-books.; SOCIAL SCIENCE / Technology Studies; Economic development; Technological innovations; China; Economics; Economics; China; Upgrading the Nation: High-Modern Developmentalism in China; Ya-Wen Lei; capitalism; development; internet; platform economy; technology; Electronic books